Ultraviolet-related ocular problems in children living on the coast of Southwest Sumba, Indonesia - Ratna Sitompul; Rita Sitorus; Julie Barliana; Rossalyn Andrisa; Budiman Prakoso; Hisar Daniel; Gladys Kusumowidagdo; Saleha Sungkar (Paediatrica Indonesiana, 2018)
Background A previous study has shown a high proportion of visual impairment and blindness in the adults of Southwest Sumba, Indonesia due to ultraviolet-radiation (UVR)- related ocular problems, such as cataract and pterygium. Currently, there is no data regarding the effect of ultraviolet (UV) exposure on children and its future implications. Objective To seek the predisposing factors of UVR ocular problems in the children of Southwest Sumba. Methods A population-based cross-sectional study was conducted in Perokonda Village, Southwest Sumba in May 2017. A total of 337 children <16 years old were examined for ocular problems by ophthalmologists. Subjects with ocular problems were then treated accordingly. Results Visual acuity was normal in 98.2% of subjects. Visual impairment and blindness were found in 1.2% and 0.3% of subjects, respectively. Ocular problems were found in 38%, consisting of conjunctival pigment deposits (60.2%), pinguecula (15.6%), and pterygium (13.3%). The UVR ocular problems constituted 33.8% of all ocular problems, comprising conjunctival pigment deposits (22.8%), pinguecula (6%), and pterygium (5%). Conclusion The proportion of UVR ocular problems in the children of Perokonda village is 34.5%, the most common of which being conjunctival pigment deposits. Such deposits may be early signs of UVR ocular problems. This study serves as a platform to highlight the possible relationship between pigment deposits and future UVR ocular problems, which warrants further study.